Os animais não humanos como sujeitos de direito: o necessário reconhecimento pela legislação brasileira - Alfaix, Francesca de Castro (2024)
This dissertation proposes the argument for the possibility of recognizing non-human animals as subjects of law by the national legal system and, consequently, the necessary modification of legislation for the reconsideration as not-a-thing of these beings. To this end, a historical-evolutionary analysis of animal rights in Brazil was carried out, highlighting the treatment of the topic by the Brazilian Federal Constitution of 1988, the Brazilian Civil Code of 2002, as well as jurisprudential and doctrinal discussions that demonstrated resistance or contributed, until then, towards a less human-centered view of the Brazilian Law. In this sense, from the exposure of the discussions brought by movements in favor of overcoming anthropocentrism, given the urgency of a paradigm shift resulting from environmental degradation, it was noted that adherence to what was proposed by these movements, biocentrism and ecocentrism, through the Brazilian Law would facilitate the design of new paths that seek to provide greater protection to other forms of life. Furthermore, the examination of the historical evolution and theoretical references of the animal issue at the international level, with greater attention to the specificities of Swiss, German, and Portuguese legislations, highlights that advances in the legal treatment of non-human animals in Comparative Law contrast with the current resistance to change on the part of Brazilian legislators and legal scholars. Thus, after inquiries into: (i) advances and resistance in the domestic legal system; (ii) the questions raised by anti-anthropocentrism movements; and (iii) the perspectives brought by the way in which the countries Switzerland, Germany and Portugal have legislated on non-human animals, it is clear that it is essential to create a regulation that consolidate non-human animals as subjects of rights and recognize them as sentient beings of inherent value to then remedy the contemporary legal obstacles that summarize these beings as mere chattels. For this research, the critical and expository method was used